Contractual penalty and the right to payment for delays caused by force majeure in Czech Civil Law under the New Civil Code - Martin Janků (DANUBE: Law, Economics and Social Issues Review, 2015)
In the context of the conclusion of contracts between entrepreneurs under the Czech Civil Code, it is a relatively common arrangement that the parties disclaim any and all liability for damage arising from non-compliance with contractual obligations, if they can prove that this failure was due to an obstacle independent of their will. This circumstance excluding liability for the damage is called force majeure by the theory. In many countries this circumstance is ruled upon directly by the legislation (höhere Gewalt, vis major). The Czech regulations represented by the new Civil Code of 2012 (CivC), however, contains only a framework provision that mentions discharging reasons. The paper deals with the - rather disputable - issue that the force majeure does not affect the obligation to pay a contractual penalty under the new rules of the CivC. It should be therefore reflected in the arrangements for contractual penalties inter partes. To this effect the paper analyses the concepts of contractual penalties and force majeure in civil law legislation. Afterwards it compares their mutual relationship and impact on the obligations of the Contracting Parties. Finally, it draws recommendations for practice from the perspective of the contracting process.
Keywords: 330; Circumstances Excluding Liability; force majeure; Contractual Penalty; Delay in Contract Performance